K-shell spectroscopy of Au plasma generated with a short-pulse laser - Zulick, C; Dollar, F; Chen, H; Falk, K; Gregori, G; Hazi, A; Murphy, C; Park, J; Seely, J; Szabo, C; Tommasini, R; Shepherd, R; et al. (2011)
The production of X-rays from electron transitions into K-shell vacancies (Kα,β) emission) is a well-known process in atomic physics and has been extensively studied as a plasma diagnostic in low-and mid-Z materials. However, X-ray spectra from near neutral high-Z ions are very complex, and their interpretation requires the use of state-of-the-art atomic calculations. In this experiment, the Titan laser system at Lawrence Livermore National Laboratory was used to deliver an approximately 350 J laser pulse, with a 10 ps duration and a wavelength of 1054 nm, to a gold (Au) target. A transparent bent quartz crystal spectrometer with a hard X-ray energy window, ranging from 17 to 102 keV, was used to measure the emission spectrum. Kα1,α2 and Kβ1,γ1 transitions were observed over a range of target sizes. Additionally, a series of shots were conducted with a pre-ionizing long pulse (3 ns, 1-10 J, 527 nm) on the backside of the target. FLYCHK, an atomic non-LTE code, designed to provide ionization and population distributions, was used to model the experiment. K α/Kβ ratios were found to be in good agreement with the predicted value for room temperature Au targets. © 2011 Published by NRC Research Press.